Short-term Effects of Elastic Therapeutic Taping on Static and Dynamic Balance in Chronic Stroke - Roghayeh Mohammadi (Iran University of Medical Sciences, 2021)
Introduction: The current pilot study aimed to examine the short-term effects of ankle Elastic Therapeutic Taping (ETT) on static and dynamic balance. Methods: Twenty-Four individuals with chronic stroke were assigned to an experimental or control group (n=12/group); they both received Conventional Physical Therapy (CT) for 3 weeks, 3 times per week. The experimental group additionally underwent taping to the ankle of the paretic side continuously for 3 weeks. Standardized measures for static and dynamic balance were administered at pre-test and post-test and analyzed using Wilcoxon and Analysis of Covariance (ANCOVA). Results: The experimental group significantly improved on two measures, Biodex anterior-posterior static (P=0.03) and medial-lateral dynamic (P=0.04) balance indices, compared to the controls. Both groups improved within their respective groups for Berg Balance Scale and Functional Reach (P<0.05). Static balance consistently improved across measures with the experimental intervention with large effect sizes. Conclusion: Ankle ETT, combined with CT, may be effective in the short-term for improving static and dynamic balance in stroke, compared to CT alone. A future larger randomized trial with longer follow-up is required to establish this method’s effectiveness.